Pengaruh Kepemimpinan Demokratis Kepala Sekolah, Kesejahteraan Guru dan Budaya Sekolah Terhadap Kinerja Guru di Sekolah - Sofyan Jayadi; Muhammad, Muhammad; Citriadin , Yudin (Al-Riwayah : Jurnal Kependidikan, 2025)
This study aims to determine the effect of democratic leadership of school principals, teacher welfare, and school culture on teacher performance at SMPN in Bayan District, North Lombok. This research employs a quantitative approach with a quasi-experimental research design. The population in this study consists of 102 respondents, and the entire population is used as the research sample (saturation sampling technique). The research instrument is a questionnaire administered directly to respondents after conducting validity and reliability tests. The data obtained were tested using three prerequisite tests: normality, multicollinearity, and heteroscedasticity. The hypothesis tests used in this study are the F test and the T test, analyzed using SPSS 16.0. The results of this study indicate that: (1) partially, the democratic leadership of school principals does not have a positive effect on teacher performance; (2) partially, teacher welfare has a positive effect on teacher performance; (3) partially, school culture has a positive effect on teacher performance. Simultaneously, the democratic leadership of school principals, teacher welfare, and school culture have a positive effect on teacher performance with a calculated F value greater than the table F value (36.059 > 3.09) with a significance value less than 0.05 (0.000 < 0.05). The implications of this study highlight the need to improve teacher welfare and develop a better school culture to optimize teacher performance. A positive and inclusive school culture can create an environment where all members of the school, including teachers, staff, and students, feel valued and motivated to participate in decision-making.